THE ROLE AND IMPORTANCE OF MUSIC CULTURE IN SCHOOL (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article is about the art of music and the activities of music literacy in music education in secondary education. In Uzbekistan, as in all areas, music education is widespread. Comprehensive updates and positive changes are taking place. Music lessons provide information on ways to further strengthen music literacy and provide knowledge to students.